Systematization of Globalization Processes in Industrial Concentration - S. V. Khudyakov (Вестник Российского экономического университета имени Г. В. Плеханова)
Russia tries to find its own niche in processes of international labour distribution relevant to its intellectual, industrial and scientific potential in order to become a full-fledged participant of global economy, to use advantages of the international exchange, which could provide economic growth and effective reforming of the national economy structure. It implies the necessity to develop the advanced system of international collaboration institutions and shape a set of efficient tools to control processes of Russian economy integration into the global economic system in condition of globalization, as well as to work out a well-grounded state strategy in the field of regional policy. The article investigates planning of concentration processes, managing these processes on scientific basis and choosing the optimum size of enterprises. The mentioned-above issues are very important in the system of industrial production planning. Planning of industrial concentration requires thorough parameter estimation. Some factors are effective in all industries, others - within the frames of certain industries or groups of related ones. The economic effect of concentration is connected with raising technical and economic indicators in product manufacturing as a result of increasing the size of production and enterprises. The author proves that concentration of big production capacities, material and labour resources at one enterprise could provide more effective and economical use of key production components (equipment, raw materials and lab our). At the same time opportunities to raise labour productivity and cut costs were identified.